PENGARUH LATIHAN KELINCAHAN DI MEDIA PASIR DAN AIR TERHADAP KELINCAHAN PEMAIN BOLA BASKET - Pratama, Ryan; Hardiyono, Bayu; Martinus, Martinus (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2017)
This research method is an experiment with the design of Two Group Pretest-Post test Design. The sample of this study were 20 athletes taken with total sampling technique. The agility measure instrument used in this study is the Illinois Agility Run Test. Data analysis technique used is t test. The results showed that (1) There was aneffect of exercise usings and media against agility Bina Darma basketball athletes, with significance 0.00 <0.05. (2) There is an effect of agility exercise using water media against the agility of Bina Darma basket ball players, with the significance of 0.03 <0.05. (3) There is a difference in the effect of agility exercise using sand and water media against the agility of Bina Darma basket ball players, with the significance of 0.00 <0.005. To improve agility more precisely if practiced using sand media.